Charged Proca stars - Salazar Landea, Ignacio (2016)
In this paper, we study gauged solutions associated with a massive vector field representing a spin-1 condensate, namely, the Proca field. We focus on regular spherically symmetric solutions which we construct either using a self-interaction potential or general relativity in order to glue the solutions together. We start generating nongravitating solutions—so-called Proca Q-balls and charged Proca Q-balls. Then we turn on backreaction on the metric, allowing gravity to hold together the Proca condensate, to study the so-called Proca stars, charged Proca stars, Proca Q-stars, and charged Proca Q-stars.